Orthognathic surgery-first approach with lingual appliances: a case report - Pamukçu Hande; Özsoy Serhat; Tüz Hakan H.; Polat-Özsoy Ömur (Sciendo, 2022)
A surgery-first approach has many advantages related to a shortened treatment time and an immediate facial aesthetic improvement compared to a three-stage conventional orthognathic surgery protocol.